Peran Guru PAI dalam Meningkatkan Karakter Religius Siswa SMK Karsa Mulya Palangkaraya - Ervina Nur Khasanah; M. Ali Sibram Malisi; Muhammad Redha Anshari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study examines the role of Islamic Religious Education teachers in improving the religious character of students at SMK Karsa Mulya Palangka Raya. Religious character involves an attitude of obedience to religious teachings, and good behavior such as good manners and obedience to worship. This research is important because the low religious character of students is influenced by foreign cultures and moral degradation, so teachers as the main figures of education need to shape students into intelligent and noble individuals. Using a descriptive qualitative method with case studies, data was collected through interviews, observations, and document analysis to identify the role of teachers as well as supporting and inhibiting factors. The main findings show that in improving religious character, PAI teachers perform the role of teachers as educators, guides, advisors, and role models, where this example is what becomes a habit for students such as repentance prayers, dhuha, congregational dzuhur, routine Friday recitation, and others. Supporting factors include cooperation between teachers, family and community support, and adequate school facilities. However, inhibiting factors such as the influence of negative associations, lack of student awareness, and diversity of student backgrounds hinder optimal achievement.